Defining the blanking period duration after cryoballoon pulmonary vein isolation in patients taking an antiarrhythmic drug. (24th May 2021) - Musat, D; Milstein, NS; Saberito, M; Bhatt, A; Habibi, M; Preminger, MW; Sichrovsky, T; Shaw, R; Mittal, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cryoballoon pulmonary vein isolation (CB) is an accepted method for ablation in patients with atrial fibrillation (AF). A three-month blanking period (BP) is commonly used in clinical trials and practice. However, the actual BP duration in patients (pts) on an antiarrhythmic drug (AAD) at time of ablation remains undefined. Objective: To objectively define the BP duration in pts undergoing CB while taking an AAD. Methods: We enrolled consecutive pts with AF who had CB PVI while on an AAD. All pts had an implantable loop recorder (ILR). We prospectively followed all pts and determined the time to last AF episode during the 90-day post-PVI BP. This was then correlated with likelihood of having an AF recurrence between 3-12 months post-PVI. Results: The cohort included 92 pts (66 ± 10 years; 62 [67%] male; 33 [36%] PAF; CHA2DS2-VASc 2.6 ± 1.7). AADs used included dofetilide (42), dronedarone (14), amiodarone (25), sotalol and propafenone (3 each), and flecainide (5). The AAD was stopped at a median of 80 [36, 105] days post-PVI.  We defined 4 distinct groups: (1) no AF in 90-day BP (n = 45 [49%]); (2) last AF within 30 days of PVI (n = 17 [18%]); (3) last AF within 60 days of PVI (n = 13 [15%]); and (4) last AF within 90 days of PVI (n = 17 [18%]). Following the 90-day BP, 47 (51%) pts had a recurrence of AF. Once recurrent AF was observed > 30 days post-ablation, patients had high likelihood of having a long term AF recurrence (p = 0.037, Figure). Conclusion: Our data suggest that the optimal BP duration in AF patients undergoing CB PVI while taking an AAD is 30 days. An AF recurrence after 30 days is associated with a very high likelihood of recurrent AF during longer-term follow-up.